TRANSLATION EXERCISES OF ENGLISH TO INDONESIAN IN DUOLINGO APPLICATION - Farrah Dina Milyarni; Asti Veto Mortini; Santi Mayasari (The Journal of English Literacy Education: The Teaching and Learning of English as a Foreign Language, 2021)
Integrating technology in learning English is needed nowadays. It can change traditional learning into modern or digital learning. Duolingo is an application that can be used to learn English. It can change the users’ perception about studying English.  The study aimed to describe the implementation of Duolingo application in translation and learning English, to find out the users’ perception about the Duolingo application, and to know the relevance criteria of Duolingo in learning English. This study used a qualitative method with 50 participants involved. The data were collected by having observation, questionnaires, and documentation. The result of observation reveals that the implementation of translation exercises was appropriate in learning English. There were two kinds of translation exercises, namely choosing the word and typewriting freely. The way it provided the translation exercises was useful in actual translation works. The users’ perception of the Duolingo application was that it was a good way to learn English using technology. Duolingo also helped the users for their English improvement. As a final point, Duolingo was relevant for learning English.